SOSIOLOGI KOMUNIKASI DALAM MEDIA INFORMASI - Frendly Albertus (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2018)
Communication is the delivery of messages between human effort. These efforts are done directly and some are using the media. Who uses the term media called mediated communication. Mediated communication in the sense that the mass media can be viewed from two perspectives, that is communication and sociology. From the point of such communication is communication using mass media, such as newspapers, radio, television and film, including books. Meanwhile, from the perspective of sociology, mass communication is a communication addressed to the masses,  suchas aspeechbefore the masses. Thus including book, because the book is addressed to the masses, the many people who took an interest and need. Along with developments led to more extensive coverage of mass communication, including books. Because the books are intended for the masses. Moreover, the books contained in the library is obviously intended for students and other campus academic community to meet a variety ofneeds.